PP127 Asthma Patient Value Framework: Lessons From Patient Focus Groups. (2019) - Kyriopoulos, Dionysios; Sogokon, Paul; Teale, Christopher; Callan, Luke
Abstract : Introduction: We sought to examine patients' perceptions of disease burden and treatment impact, and what patients value over the course of the asthma experience. Methods: Patient focus groups were conducted in three countries, the USA (n = 8 patients), the United Kingdom (n = 7 patients), and Germany (n = 7 patients), to examine aspects of disease burden and patient experience (physical, emotional, clinical, economic, and social). Cause and effect were also explored. Global Initiative for Asthma guidelines were used to screen patients by severity, based on age, sex, time since diagnosis, number of attacks, oral corticosteroid use, and number of therapies needed to control symptoms. Patients classified and ranked aspects of disease burden, including whether it was continuous or episodic in nature, and discussed the interventions used to manage their asthma. Results: The overall burden of illness was driven by the combined effect of the disease and treatment burdens. All patients highlighted the negative impact of oral corticosteroids. Patients believed that they were the key actors in their asthma management (not healthcare professionals), and reported the physical and emotional burdens as being the most dominant. Understanding of the terms "attack" or "exacerbation" differed significantly between patients, and did not necessarily match the clinical definitions. Patients considered asthma to be an individualized condition that drives lifestyle changes; disease management drives burden and vice versa. Patients perceived that burden was continuous over time, with specific phases of variable duration—before, during, and after an attack—whereas other stakeholders had a more episodic focus. Patients expected more holistic and personalized approaches for managing their asthma. Conclusions: The research indicated a misalignment between what patients value and what clinicians, payers, and regulators consider in their assessments and decisions. Greater alignment among the different stakeholders, and more inclusion of patients' values in decision making, will improve outcomes.